일부지역 치위생과 학생들에 대한 치위생 교육과정의 팀기반학습이 학습동기와 자기주도 학습력에 미치는 효과 - 박인숙; 김동기 (Han'guk Ch'iwisaeng Hakhoe chi, 2010)
Objectives : The purpose of this study was to apply team-based learning to dental hygiene students in theoretical oral prophylaxis class, one of required courses geared toward acquiring professional knowledge on preventive public health, as oral prophylaxis was counted among major duties of dental hygienists. It's ultimately meant to compare the effects of team- based learning and expository instruction on the learning motivation and self-directed learning capabilities of learners in order to discuss the effects of team-based learning in dental hygiene education. Method : The subjects in this study were 60 dental hygiene students at C college. Out of them, 32 students who were freshmen as of 2007 were grouped into an experimental group, and 28 students who were freshmen as of 2006 were selected as a control group. The experimental group was engaged in team-based learning from August 30 to December 6, 2007, and the control group took expository lessons from August 28 to December 8, 2006. Their learning motivation and self-directed learning capabilities were evaluated by using t-test, paired t-test and GLM analysis. Results : The findings of the study were as follows:1. The experimental group scored better in learning motivation than the control group after they were engaged in team-based learning (p<.001). According to GLM analysis, there was a significant intergroup gap in learning motivation, and the two groups were statistically significantly different in its subfactors involving attention, relevance and confidence(p<.05). 2. The experimental group excelled the control group at self-directed learning capabilities(p<.05), and the team-based learning had a better effect on self-directed learning capabilities than the expository instruction. Conclusion : Given the findings of the study, the team-based learning was more effective than the expository instruction at boosting the learning motivation and self-directed learning capabilities of the students. Therefore revised teaching methods should be prepared in consideration of the characteristics of dental hygiene courses, and the development of new instructional models and educational programs is required as well. KCI Citation Count: 18